INTERNALISASI PESAN MULTIKULTURAL PADA ORGANISASI PESANTREN PUTRI STAIN JEMBER - Musyarofah Musyarofah (IAIN Salatiga, 2016)
Multicultural education focuses on the process of developing Islamic boarding school students’ ability to comprehend, admit, respect, and live harmonically and peacefully in different reality. Islamic boarding school has important role to internalize multicultural values. This research was aimed to know the internalization of multicultural education among Islamic boarding school students in the Islamic boarding school Organization for female at State Islamic Studies Institute (STAIN) Jember. This research used qualitative approach where the tutor, committee, and thestudents of this organization became the research subject. This research revealed that the internalization of multicultural education in curriculum was implemented in diniyah and Islamic literature study (kajian kitab) by integrating multicultural values in the study ofTaisirul Kholaq, Tadhib, Al-Akhlaqu Lil Banats, Fiqhun nisa, Kifayatu al-atsqiya, and Fathul Qorib book. Integration of multicultural value in educational process was implemented in some matters: (1) creating Islamic boarding school culture that respected the difference; (2) Educational activity implemented by kyai emphasized on the importance of honor aspect toward humanity. (3) The enactment of regulation and punishment dedicated to all students, without seeing their background and socio-economic status.